Micronutrients in health and disease. - Prasad, Kedar N., 1935- (Boca Raton : CRC, 2011)
Increased oxidative stress due to the production of excessive amounts of free radicals along with the effects of chronic inflammation play a major role in the initiation and progression of a host of disease states, ranging from cancer to posttraumatic stress disorder. In varying doses, micronutrients, including antioxidants, B vitamins, and minerals have shown to help ameliorate these effects. However, clinical studies using isolated micronutrients to combat these illnesses have proven that such limited therapy has produced inconsistent results. Assembling a plethora of rational and scientific evidence, Micronutrients in Health and Disease makes the case that the use of not one but multiple micronutrients working together synergistically in combination with a low-fat, high-fiber diet can prove successful in the prevention and management of these chronic conditions. Following an overview of basic facts about micronutrients, oxidative stress, inflammation, the immune system, and the results of various clinical studies, the book explores the use of micronutrients in prevention and improvement of standard therapy in a number of disease states, including: Coronary artery disease Diabetes Cancer Alzheimer's disease Parkinson's disease Hearing disorders Posttraumatic stress disorder Traumatic brain injury HIV/AIDS Adverse effects of radiation Arthritis Steeped in research and heavily referenced, this volume concludes with a list of common myths and misconceptions about micronutrient use and a chart with dietary reference intakes (DRIs) of all the major products, making this a solid resource for those seeking to promote healthy aging and prevent and manage disease.